Shared and cell type-specific adaptation strategies of Gag and Env yield high titer bovine foamy virus variants - Bao, Qiu Ying; Hotz-Wagenblatt, Agnes; Betts, Matthew J.; Hipp, Michaela; Hugo, Annette; Pougialis, Georgios; Lei-Rossmann, Janet; Löchelt, Martin (Infection, genetics and evolution, 2020)
During in vitro selection and evolution screens to adapt the tightly cell-associated bovine foamy virus BFV to high titer cell-free transmission, common, cell-type specific and concurrent adaptive changes in Gag and Env, the major players of foamy virus particle assembly and release, were detected. Upon early establishment of cell type-independent pioneering mutations in Env and, subsequently in Gag, a diverse virus pool emerged that was characterized by the occurrence of shared and additional cell type-specific exchanges. At late passages and saturated titers, remarkably homogeneous virus populations characterized by functionally important mutations developed which may be partly due to stochastic evolutionary events that occurred earlier during adaptation. Reverse genetics showed that defined mutations were functionally important for high titer cell-free transmission.